Congestive Heart Failure Exhibited Higher BMI With Lower Energy Intake and Lower Physical Activity Level: Data From the National Health and Examination Nutrition Survey - Xu, Tianyu; Zhou, Haobin; Ma, Zhuang; Zhang, Hao; Zeng, Qingchun; Xu, Dingli; Zhang, Yuhui; Zhang, Jian (Frontiers in Cardiovascular Medicine, 2021)
Background: Despite nutritional deficiency existed in congestive heart failure (CHF), there is a large amount of CHF patients suffer from obesity. This study aimed to identify the differences for increased BMI or obesity in CHF patients. Methods: This cross-sectional study included adults from the National Health and Nutrition Examination Survey 2007-2016. Differences were compared between CHF participants versus non-CHF participants, and BMI ≥ 30kg/m2 versus BMI < 30kg/m2 CHF participants. Results: CHF participants were with higher BMI, lower energy and macronutrients intakes, lower physical activity level and longer rest time, lower hematocrit and hemoglobin level (all P <0.05) than non-CHF participants. The prevalence of BMI ≥ 30kg/m2 in patients with CHF was 53.48%. There was no significant difference observed in energy, macronutrients intake between CHF patients with BMI ≥ 30kg/m2 or < 30kg/m2. The water intake (P =0.032), sedentary time (P =0.002), and hematocrit (P =0.028) were significantly different between CHF with BMI ≥ 30kg/m2 and with < 30kg/m2.. Conclusion: Compared with non-CHF participants, CHF patients exhibited higher BMI with lower energy and macronutrients intakes, lower physical activity level, longer rest time and hemodilution with lower hematocrit and hemoglobin level. Among CHF patients with BMI ≥ 30kg/m2, higher sedentary time and hematocrit were observed.